Predictors of outcome after liver transplantation for hepatocellular carcinoma (HCC) beyond Milan criteria. (October 2020) - Halazun, K.J.; Sapisochin, G.; von Ahrens, D.; Agopian, V.G.; Tabrizian, P.
Abstract: The Milan criteria have been the cornerstone of selection policies for patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT) globally for over two decades. Many groups have proposed the transplantation of patients with larger and more numerous tumors achieving comparable results. Many of these use radiologic morphometric criteria as surrogates for explant pathology to predict outcomes. Several other indices have been developed both within and beyond Milan incorporating biological indices as well as dynamic markers of response to pre-transplant locoregional treatments and waiting time. These have allowed for successful expansion of transplant selection criteria without compromising outcomes with limited organ supplies. In this review we will discuss the predictors of outcome in patients beyond Milan criteria. Highlights: Milan criteria for transplantation in HCC can be restrictive. New criteria have been developed with comparable or superior results. Biological indices, response to locoregional therapy and waitlist time are important outcome predictors.